Le rôle de l’enchaînement rhématique dans la structure informationnelle de discours - Miczka, Ewa (Neophilologica, 2010)
In this paper the author analyses the role of rhematic part in the information structure of discourse defined as the thematic-rhematic hierarchical structure. The main area of author`s interest is connected with the levels of thematic-rhematic structures which are not limited to the sentence level. The structures in question are organized in groups of sentences which are subordinate to partial themes. The author will show not only the preliminary list of possible thematic-rhematic configurations appearing in the place where these groups contact, but also an example of the analysis of discourse information structure.